Outcome of early identification and intervention on infants with hearing loss under universal hearing screening program - Poonual W. (2017)
© 2017, Medical Association of Thailand. All rights reserved. Objective: To determine the outcome of early identification and intervention of hearing loss children. Material and Method: An analytic prospective study. All neonates were screened withTEOAE/ABR. All infants were diagnosed and started early intervention at sixth month and followed for hearing and developmental evaluation until eighteen months of age. Results: Three thousand one hundred twenty neonates underwent hearing screening tests. One hundred and three infants had abnormal of 6 months of age and were diagnosed with congenital hearing loss (89 mild hearing loss, 12 moderate hearing loss, 1 moderate-severe hearing loss and 1 profound hearing loss). They received early intervention (8 hearing aid fitting (0.3%), 103 auditory training (3.3%), 103 counseling (3.3%) and 103 combine (3.3%) at 6 months of age). During follow up, eighty nine infants who had abnormal initial hearing tests were found to have normal hearing at eighteen months of age, Only Fourteen infants (0.4%) had permanent hearing loss. There were 7, 5, 1 and 1 infants in the mild, moderate, moderate-severe and profound hearing loss groups. The interventions offered to infants with different levels of hearing impairment were 5 hearing aid fittings (35.7%), 14 auditory training (100%), 14 counseling (100%) and 14 combination of three methods (100%). The development after 12 months follow up in infants with different levels of hearing impairment were 14 auditory improvement (100%), 14 speech improvement (100%) and 5 language improvement (35.7%). The common risk factors ranked in order of frequency are craniofacial anomalies(RR 2.57, 95%CI 1.49-4.43), ototoxic exposure(RR 4.71, 95%CI 1.94-11.46), severe hyperbilirubinemia (RR 2.10, 95%CI 1.08-4.06), low APGAR score at 5 minutes (RR 2.42, 95%CI 1.03-5.68) and sepsis (RR 2.02, 95%CI 1.01-4.03). Conclusion: Continuing evaluation of hearing and development during follow-up is important in children with abnormal hearing tests. Early intervention can prevent acoustic deprivation and improve language development.